2016
DOI: 10.1021/acsbiomaterials.6b00052
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Therapy of Glioblastoma Multiforme Using Multiwalled Carbon Nanotubes Optimized for Diffusion in Extracellular Space

Abstract: Glioblastoma multiforme (GBM) is the most common and most lethal primary brain tumor with a 5 year overall survival rate of approximately 5%. Currently, no therapy is curative and all have significant side effects. Focal thermal ablative therapies are being investigated as a new therapeutic approach. Such therapies can be enhanced using nanotechnology. Carbon nanotube mediated thermal therapy (CNMTT) uses lasers that emit near infrared radiation to excite carbon nanotubes (CNTs) localized to the tumor to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 75 publications
2
51
0
Order By: Relevance
“…Nevertheless, many of these models, even if they are targeted toward specific tumor mass, may face challenges in confining heat production at the very local levels; studies show that during the photothermal treatments of the cells using the nanoparticles, the temperature of the entire field is raised by a significant amount. [48][49][50][51] This could raise serious concerns about damage upon nearby, non-targeted tissue as the entire field is being affected. Our method tries to overcome this drawback by promoting target-specific attachment of the nanoparticle products to the tumor: This had led to dramatic reduction in overall heat generation of the field (Figure 5), while producing enough thermal energy at proximity to the target to induce sufficient damage on the tumor while minimizing temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many of these models, even if they are targeted toward specific tumor mass, may face challenges in confining heat production at the very local levels; studies show that during the photothermal treatments of the cells using the nanoparticles, the temperature of the entire field is raised by a significant amount. [48][49][50][51] This could raise serious concerns about damage upon nearby, non-targeted tissue as the entire field is being affected. Our method tries to overcome this drawback by promoting target-specific attachment of the nanoparticle products to the tumor: This had led to dramatic reduction in overall heat generation of the field (Figure 5), while producing enough thermal energy at proximity to the target to induce sufficient damage on the tumor while minimizing temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…PEG functionalized SWCNTs also did not induce significant morphological alterations in rat hippocampus(Dal Bosco et al, 2015). Similarly, we found that DSPE-PEG coated, acid oxidized MWCNTs were cytotoxic to glioblastoma cells grown in two-dimensional monolayer, but had no observable effect on growth of glioblastoma cells grown as three-dimensional spheroids(Eldridge et al, 2016). However, astrocytes exposed to PEG functionalized SWCNTs may mature and increase glial cell activity(Gottipati et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…CNTs generate tremendous heat upon exposure to near infrared radiation, making them useful for photothermal cancer therapy(Burke et al, 2012; Singh and Torti, 2013). We and others demonstrated the potential to use CNTs for photothermal treatment of glioblastoma, a deadly brain tumor(Eldridge et al, 2016; Santos et al, 2014; Wang et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the properties of carbon nanomaterials and their potential applications in PDT have been analyzed in an attempt to substitute current invasive thermal procedures that remove tumors or cancer cells of breast cancer [70][71][72][73][74][75][76][77][78][79][80][81]. Due to the carbon nanomaterials presence in the PDT, cancer cells accumulate light-sensitive molecules (carbon nanomaterials) which, in the presence of oxygen, absorb the radiation of an infrared camera and turn it into heat.…”
Section: Photodynamicmentioning
confidence: 99%